A membrane glucocorticoid receptor mediates the rapid/non‐genomic actions of glucocorticoids in mammalian skeletal muscle fibres. (23rd August 2013) - Pérez, María Hernández‐Alcalá; Cormack, Jonathan; Mallinson, David; Mutungi, Gabriel
Key points Glucocorticoids are stress hormones used in the treatment of many chronic inflammatory diseases including asthma. They exert most of their physiological/pharmacological actions by regulating the activity of genes involved in the inflammatory response. However, they also have rapid/non‐genomic effects whose functions are poorly understood. In this study we used two widely prescribed glucocorticoids, beclomethasone dipropionate and prednisolone acetate, to investigate whether these hormones have rapid/non‐genomic effects in mammalian skeletal muscles. Both glucocorticoids increased maximum force in slow‐twitch muscle fibres/cells without significantly affecting that of fast‐twitch muscle fibres. The increase in force occurred within 10 min and was blocked by an inhibitor of the glucocorticoid receptor and a protein (antibody) that binds the receptor. These findings suggest that these hormones/drugs have rapid/non‐genomic effects in mammalian skeletal muscles; these effects are mediated by a membrane glucocorticoid receptor and are physiologically/pharmacologically beneficial, especially in slow muscles. Abstract Glucocorticoids (GCs) are steroid hormones released from the adrenal gland in response to stress. They are also some of the most potent anti‐inflammatory and immunosuppressive drugs currently in clinical use. They exert most of their physiological and pharmacological actions through the classical/genomic pathway. However, they also have rapid/non‐genomic actions whose physiological and pharmacological functions are still poorly understood. Therefore, the primary aim of this study was to investigate the rapid/non‐genomic effects of two widely prescribed glucocorticoids, beclomethasone dipropionate (BDP) and prednisolone acetate (PDNA), on force production in isolated, intact, mouse skeletal muscle fibre bundles. The results show that the effects of both GCs on maximum isometric force (Po) were fibre‐type dependent. Thus, they increased Po in the slow‐twitch fibre bundles without significantly affecting that of the fast‐twitch fibre bundles. The increase in Po occurred within 10 min and was insensitive to the transcriptional inhibitor actinomycin D. Also, it was maximal at ∼250 nm and was blocked by the glucocorticoid receptor (GCR) inhibitor RU486 and a monoclonal anti‐GCR, suggesting that it was mediated by a membrane (m) GCR. Both muscle fibre types expressed a cytosolic GCR. However, a mGCR was present only in the slow‐twitch fibres. The receptor was more abundant in oxidative than in glycolytic fibres and was confined mainly to the periphery of the fibres where it co‐localised with laminin. From these findings we conclude that the rapid/non‐genomic actions of GCs are mediated by a mGCR and that they are physiologically/therapeutically beneficial, especially in slow‐twitch muscle fibres.